A comparative study of the apical seals of canals enlarged through the modified conventional and the step-back techniques - Sembrano, Marilou H.; Moreno, Ma. Zellita T.; Manuel, Loida (Adviser).
This in vitro study compared the integrity of apical seals of root canals enlarged through the modified conventional technique and the step-back technique. Twenty-five upper maxillary incisors were enlarged through the modified conventional technique and another twenty five upper maxillary incisors were enlarged using the step-back technique. After obturation with gutta percha cones, the teeth were immersed in India Ink, longitudinally sectioned and analyzed for the extent of dye penetration. Analysis of the results show that there is no significant difference between the apical seals of canals enlarged through the modified conventional technique and the step-back technique.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Root canal therapy -- Methods